東日本大震災のリスクに深く関連した組織への信頼 - 中谷内, 一也; 工藤, 大介; 尾崎, 拓 (心理学研究, 2014)
This study investigated the levels of public trust in organizations associated with the Great East Japan Earthquake. In Study 1 (N = 639), the levels of trust in eight organizations as well as the determinants of trust–perceived salient value similarity (SVS), ability, and motivation– were measured twice, first immediately after the earthquake and then a year later. The results indicated that the trust levels for six of the eight organizations had been preserved, supporting the double asymmetric effect of trust. The results of structural equation modeling (SEM) revealed that SVS explained trust more when the organization had been less trusted. Trust in the organization explains well the perceived reduction of the target risk. The results of SEM in Study 2 (N = 1,030) replicated those of Study 1, suggesting the stability of the explanatory power of the determinants of trust. Implications of the study for risk management practices are discussed.